Parenthood preparedness in young muslim families - Septyaninda, Taqwa Hasma; Kumaidi, Kumaidi (Asosiasi Psikologi Islam (API) Himpsi, 2017)
The purpose of this research is to describe important points of parenthood preparedness in Muslim young families. Data were collected through qualitative methods and involve two Muslim young families to interview. Results show that the important points toward parenthood preparedness are selective in choosing a partner, looking for information from various sources, self improvement, and learn from their parents. These important points is being influenced by socioeconomic aspect, psychologycal characteristic, intelectual, and motivation. Keywords: Preparedness, Parenthood Preparedness, Muslim Young Families